Prevalence of Hypertension and Diabetes and Coexistence of Chronic Kidney Disease and Cardiovascular Risk in the Population of the Republic of Moldova. (28th November 2012) - Codreanu, Igor; Sali, Vera; Gaibu, Sergiu; Suveica, Luminita; Popa, Sergiu; Perico, Norberto; Ene-Iordache, Bogdan; Carminati, Sergio; Feehally, John; Remuzzi, Giuseppe
Abstract : In 2005, the International Society of Nephrology (ISN) established the Global Outreach Program (GO) aimed at building a capacity for detecting and managing chronic kidney disease and its complications in low- and middle-income countries. Here we report data from the 2006-2007 screening program (1025 subjects from the general population) in the Republic of Moldova aimed to determine the prevalence of hypertension, diabetes, and their coexistence with microalbuminuria. The likelihood of a serious cardiovascular (CV) event was also estimated. Hypertension and diabetes were very common among screened subjects. The prevalence of microalbuminuria was 16.9% and that of estimated GFR <60 ml/min/1.73 m 2 (decreased renal function) was 9.4%. Male gender was associated with an increased prevalence of hypertension and microalbuminuria. Hypertension and diabetes clustered in subjects with microalbuminuria and renal dysfunction. Risk factors such as preobesity/obesity, physical inactivity and smoking were relatively common, even in younger participants. The prevalence of subjects with predicted 10-year CV risk ≥ 10% was 10.0%. In conclusion, in the Republic of Moldova patients with hypertension and diabetes should be screened for the coexistence of renal abnormalities, with the intention of developing disease-specific health-care interventions with the primary goal to reduce CV morbidity and mortality and prevent renal disease progression to end stage renal disease.